Mobile NMR: An essential tool for protecting our cultural heritage. (19th December 2016) - Baias, Maria
Abstract: What is 'cultural heritage'? Is it simply our legacy of physical artifacts – or is it our collective legacy as human societies – how we want to be remembered by future generations? With time, negligence, and even military conflict working to erase the past, we must ask: Can a better understanding of our shared heritage assists us in addressing cultural differences in the present day? And how can science both help us understand the historic record and work to preserve it? In this perspective article, we examine an emerging scientific method, mobile nuclear magnetic resonance (NMR), which can help us examine in a non‐invasive way important objects and sites of our cultural heritage. Following these investigations, one can envisage ways for protecting our global heritage for future generations. For this purpose, we examine how this method can be used to non‐destructively explore historical artifacts, which can lead to understanding the science behind the creation of these treasured items – paintings, frescoes, parchments, historical buildings, musical instruments, ancient mummies, and other artifacts. This perspective article follows few relevant examples from the scientific literature where mobile NMR has been applied in a non‐invasive way to analyze objects of cultural heritage. One can envision possible future advancements of this technique and further applications where portable NMR can be used for conservation of cultural heritage. © 2016 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd. Abstract : This perspective article focuses on the challenges and perspectives of mobile nuclear magnetic resonance (NMR) as a tool for scientific investigations of assets of cultural heritage. Few relevant examples from the scientific literature where mobile NMR has been applied in a non‐invasive way to analyze objects of cultural heritage are discussed. Potential future advancements of this technique and further applications where portable NMR can be used for conservation of cultural heritage are proposed.